The effects 0f RA 9136 (EPIRA) on organizational effectiveness adescriptive comparative case study of Iloilo Electric cooperative I. - Bagundang, Farizah Joy P. (2012.)
The national energy problem led to the reform of the Philippine power industry through RA 9136 of 2001 (EPIRA), aimed at improving energy supply and lowering electricity rated through private sector participation in service delivery. This study examined the case of Iloilo Electric Cooperative (ILECO) 1, one of the largest cooperatives in the Province of Iloilo, in evaluating the effects of institutional reform to organizational effectiveness. The study utilized key informant interviews to obtain primary data on institutional reforms and community survey to gather primary data on ILECO 1?s services and consumer welfare. A total of 132 residential and commercial respondents in the Municipality of Miagao, randomly selected based on the total number of registered business and household population of barangay, participated in a community survey. The results posit that centralization, instead of decentralization, improves organizational efficiency. Nevertheless, decentralization improved consumers? access to electricity while restructuring improved the cooperative?s access to energy supply. However, decentralization and restructuring are ineffective in lowering electricity rates and in responding to consumer complaints. Despite this, survey shows that the cooperative?s performance significantly improved today than five years ago. This study contributes to the understanding of the national problem on energy and on the effectiveness of institutional reforms.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2012.
Keywords: Iloilo Electric Cooperative I -- Research; RA 9136.; Electric Power Industry Reform Act